The First United Arab Emirates National Representative Birth Cohort Study: Study Protocol - Mutare, Sharon; Feehan, Jack; Cheikh Ismail, Leila; Ali, Habiba I.; Stojanovska, Lily; Shehab, Abdullah; Khair, Howaida; Ali, Raghib; Hwalla, Nahla; Kharroubi, Samer; Hills, Andrew P.; Fernandes, Michelle; et al. (Frontiers in Pediatrics, 2022)
In recent years, the prevalence of non-communicable diseases has escalated, and in the Middle East and North African region, the United Arab Emirates (UAE) have been ranked fifth highest for diabetes mellitus. Evidence suggests that there are strong associations between nutrition in early life and the risk of disease in adulthood. This manuscript describes the study protocol of the First United Arab Emirates National Representative Birth Cohort Study (UAE-BCS), with the objective of investigating nutrition and lifestyle factors in the first 1000 days of life. The main aims of the study are 1) to address critical issues relating to mother and child nutrition and their effect on growth and development, 2) to profile maternal nutrition, child growth, health, and development outcomes in early life, and 3) to study the associations between these factors among the Emirati population in the UAE. A multidisciplinary team of researchers from the UAE, Lebanon, Australia, and the United Kingdom was created to implement the study. We aim to recruit 260 pregnant Emirati women within their first trimester, which is defined by the study as from 8 to 12 weeks pregnant, from obstetrics and gynecology clinics in the UAE. Participants will attend a total of 11 visits with 1 visit in each trimester of pregnancy and 8 visits after delivery. Maternal data collection includes, socio-demographic and lifestyle factors, dietary intake, anthropometric measurements, physical activity, maternal psychological state, and blood samples for biochemical analysis. Post-partum, visits will take place when the child is 0.5, 4, 6, 9, 12, 18, and 24 months old, with data collection including infant anthropometric measurements, young child feeding practices, dietary intake, supplement use and the eating environment at home, as well as all maternal data collection described above, apart from blood samples. Within 2 weeks of birth, at 10-14 months and at 22 – 26 months of age, additional evaluation of infant vision, health, neurological examination, neurodevelopmental and sleep assessments will be undertaken. It is hoped that the UAE-BCS will provide concrete data to drive childhood health policy in the UAE to combat the rising cost of non-communicable disease.